INFECTIOUS NODULAR DERMATITIS OF CATTLE - Turaboeva Diyora (Journals Park Publishing, 2023)
This article talks about infectious dermatitis of cattle. In addition, the symptoms characteristic of animals with this disease, the changes that occur in the animal during the disease, and the list of drugs are given.
Keywords: Capripoxvirus, Biferon-B, lymph nodes, digestive organs, mucous membranes, Creolin.